2020
DOI: 10.1111/jan.14279
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a modified comprehensive behavioral intervention for tics for children and adolescents with tourette's syndrome: A randomized controlled trial

Abstract: Aim To evaluate the effectiveness of a modified four‐session Comprehensive Behavioral Intervention for Tics programme for decreasing tics in children and adolescents with Tourette's syndrome. Background Comprehensive Behavioral Intervention for Tics programme has been shown to decrease tic severity. However, the lack of behaviour therapists in countries, such as in Taiwan, may preclude application of the standard eight‐session, 10‐week programme. Design Randomized controlled study. Methods Participants aged 6–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 40 publications
0
21
0
1
Order By: Relevance
“…Effect sizes were not reported Andrén et al (2019) [ 59 ] Internet ERP vs. Internet HRT N = 23 Age 8–16 YGTSS-TTS : Internet ERP: 23.8 (pre) to 18.3 (3FU) Within-group effect size: 1.12 Internet HRT: 23.5 (pre) to 20.2 (3FU) Within-group effect size: 0.50 12FU : YGTSS-TTS: Internet ERP: 16.9 Internet HRT: 19.4 Duration : 10 weeks of therapist-supported (via text messages) internet-delivered treatment Interventions : In addition to the ERP or HRT core elements, both groups included functional analysis and parent training Design : Study did not aim to compare groups Results : Significant within-group effect on the YGTSS-TTS for the Internet ERP group, but not the Internet HRT group Follow-up : Effects were maintained at 12FU Nissen et al (2019, 2021) [ 43 , 52 ] Individual HRT + ERP vs Group HRT + ERP N = 59 Age 9–17 YGTSS-TTS : Individual HRT + ERP: 23.8 (pre) to 14.3 (post) Within-group effect size: 1.21 Group HRT + ERP: 23.4 (pre) to 15.9 (post) Within-group effect size: 1.38 12FU : YGTSS-TTS: Individual HRT + ERP: 12.7 Group HRT + ERP: 12.8 Duration : 8 regular sessions and 1 booster session, delivered individually or in a group format Results : No significant between-group effect on the YGTSS-TTS. Significant within-group effects on the YGTSS-TTS for each group Follow-up : Treatment effects were maintained for both groups at 12FU Limitations : Uncertain whether the study was powered to detect significant between-group effects Chen et al (2020) [ 63 ] CBIT + UC vs. UC N = 46 Age 6–18 YGTSS-TTS : CBIT: 19.3 (pre) to 10.4 (post) UC: 17.7 (pre) to 14.5 (post) Between-group effect size: 0.56 3FU : YGTSS-TTS: CBIT: 6.6 Duration : CBIT: 4 sessions (during 3 months) Interventions : CBIT included psychoeducation, habit reversal training, relaxation training, and relapse prevention; UC included psychoeducation and 50 mg of pyridoxine (per day) Results : Significant between-group effect on the YGTSS-TTS (in favor of CBIT + UC) Follow-up : Further improvement for the CBIT + UC-group in a within-group ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect sizes were not reported Andrén et al (2019) [ 59 ] Internet ERP vs. Internet HRT N = 23 Age 8–16 YGTSS-TTS : Internet ERP: 23.8 (pre) to 18.3 (3FU) Within-group effect size: 1.12 Internet HRT: 23.5 (pre) to 20.2 (3FU) Within-group effect size: 0.50 12FU : YGTSS-TTS: Internet ERP: 16.9 Internet HRT: 19.4 Duration : 10 weeks of therapist-supported (via text messages) internet-delivered treatment Interventions : In addition to the ERP or HRT core elements, both groups included functional analysis and parent training Design : Study did not aim to compare groups Results : Significant within-group effect on the YGTSS-TTS for the Internet ERP group, but not the Internet HRT group Follow-up : Effects were maintained at 12FU Nissen et al (2019, 2021) [ 43 , 52 ] Individual HRT + ERP vs Group HRT + ERP N = 59 Age 9–17 YGTSS-TTS : Individual HRT + ERP: 23.8 (pre) to 14.3 (post) Within-group effect size: 1.21 Group HRT + ERP: 23.4 (pre) to 15.9 (post) Within-group effect size: 1.38 12FU : YGTSS-TTS: Individual HRT + ERP: 12.7 Group HRT + ERP: 12.8 Duration : 8 regular sessions and 1 booster session, delivered individually or in a group format Results : No significant between-group effect on the YGTSS-TTS. Significant within-group effects on the YGTSS-TTS for each group Follow-up : Treatment effects were maintained for both groups at 12FU Limitations : Uncertain whether the study was powered to detect significant between-group effects Chen et al (2020) [ 63 ] CBIT + UC vs. UC N = 46 Age 6–18 YGTSS-TTS : CBIT: 19.3 (pre) to 10.4 (post) UC: 17.7 (pre) to 14.5 (post) Between-group effect size: 0.56 3FU : YGTSS-TTS: CBIT: 6.6 Duration : CBIT: 4 sessions (during 3 months) Interventions : CBIT included psychoeducation, habit reversal training, relaxation training, and relapse prevention; UC included psychoeducation and 50 mg of pyridoxine (per day) Results : Significant between-group effect on the YGTSS-TTS (in favor of CBIT + UC) Follow-up : Further improvement for the CBIT + UC-group in a within-group ...…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al evaluated the effects of a shortened CBIT-protocol (four instead of eight sessions). In a RCT [ 63 ], 46 participants (6–18 years) were randomized to shortened CBIT plus usual care (psychoeducation and 50 mg of pyridoxine) or usual care only. Results showed a medium-sized, significant between-group effect on the YGTSS-TTS (in favor of CBIT plus usual care; d =0.56).…”
Section: Resultsmentioning
confidence: 99%
“…For example, all eight CBIT sessions can be delivered over a small number of consecutive days (Blount et al, 2014). Additionally, one Taiwanese study showed adding a "light" version of CBIT (i.e., 4 sessions delivered across 3 months, with function-based intervention component omitted) to usual care led to greater reductions in tics and related impairment (Chen et al, 2019).…”
Section: Are There Differences Between Existing Cbit "Makes and Models"?mentioning
confidence: 99%
“…In some clinical practice settings (e.g., integrated primary care settings, managed care organizations), access to behavioral health services may be especially streamlined, creating a need to condense treatment into a smaller number of sessions than employed in research studies. There is some evidence that the streamlined, 4-session "CBIT light" can provide some benefit beyond usual care, though the extent of these benefits relative to traditional CBIT is unclear (Chen et al, 2019).…”
Section: How Do Cbit Formats Actually Work "In the Real World?"mentioning
confidence: 99%
“…The prevalence rate if this syndrome is estimated as 0.77% in children in aged 6-15 years (9). This disorder can impact on quality of health and it is associated to other psychiatric condition and self-harm behaviours which emphasis the importance of appropriate treatment (10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%